Vulvar cancer and sentinel lymph nodes: a new standard of care?. Issue 9 (September 2014) - Robison, Katina; Fiascone, Stephen; Moore, Richard
Abstract : The treatment of early-stage vulvar cancer has remained surgical over time. Fortunately, less invasive surgical options have emerged, decreasing the significant morbidity associated with treatment. In the past decade, sentinel lymph node (SLN) dissection alone in select patients with vulvar cancer has been shown to be safe, feasible and has decreased surgical morbidity. In addition, multiple recent studies have reported low groin recurrence rates in women that underwent SLN dissection alone, which are similar to groin recurrence rates seen among women that underwent complete inguinal lymph node dissection. We believe SLN dissection should be the standard of care in select patients at institutions with surgeons experienced in the SLN technique. We feel caution should be used when performing SLN dissections in large vulvar lesions and in midline lesions. Further information is needed regarding the appropriate treatment of positive sentinel lymph nodes and, in particular, on the management of micrometastases.